STRATEGIC MANAGEMENT: TYPES OF BUSINESS STRATEGIES – ADVANTAGES AND DISADVANTAGES - Sena Balcı; Nicola Ciuffreda (Journal of Bio-Based Marketing)
In the competitive landscape of modern business, organizations adopt diverse strategies to achieve their objectives and gain market advantage. This paper explores four primary types of business strategies: cost leadership, differentiation, focus, and growth strategies. Cost leadership enables firms to attract a broad customer base through low prices but may compromise quality and innovation. Differentiation allows companies to build strong brand loyalty by offering unique products; however, it carries risks of imitation and high operational costs. Focus strategies target specific market niches, fostering customer loyalty but limiting growth potential and increasing vulnerability to market shifts. Growth strategies, encompassing mergers and expansions, aim to enhance market share but can strain resources and lead to neglect of core operations. Understanding the advantages and disadvantages of these strategies is crucial for organizations to navigate challenges effectively and sustain long-term success.